2009
DOI: 10.1214/08-aoas222
|View full text |Cite
|
Sign up to set email alerts
|

Handbook for the GREAT08 Challenge: An image analysis competition for cosmological lensing

Abstract: 12 pages of main text plus 19 pages of appendices/references. Please see http://www.great08challenge.info for the first release of simulations, list of changes to this document and a version with higher resolution figures. AOAS accepted subject to minor revisionInternational audienceThe GRavitational lEnsing Accuracy Testing 2008 (GREAT08) Challenge focuses on a problem that is of crucial importance for future observations in cosmology. The shapes of distant galaxies can be used to determine the properties of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 45 publications
0
106
1
Order By: Relevance
“…This evolution has been demonstrated through a series of community challenges (Heymans et al 2006;Massey et al 2007b;Bridle et al 2009Bridle et al , 2010Kitching et al 2010Kitching et al , 2012Mandelbaum et al 2014Mandelbaum et al , 2015. In the most recent of these, GREAT3, the types of methods used included those based on estimation of per-galaxy shapes via measurements of moments, fitting parametric light profiles, decomposition into basis functions, and machine learning, as well as methods that involve inferring ensemble shears without per-galaxy shapes.…”
Section: Shear Estimation Algorithmmentioning
confidence: 99%
“…This evolution has been demonstrated through a series of community challenges (Heymans et al 2006;Massey et al 2007b;Bridle et al 2009Bridle et al , 2010Kitching et al 2010Kitching et al , 2012Mandelbaum et al 2014Mandelbaum et al , 2015. In the most recent of these, GREAT3, the types of methods used included those based on estimation of per-galaxy shapes via measurements of moments, fitting parametric light profiles, decomposition into basis functions, and machine learning, as well as methods that involve inferring ensemble shears without per-galaxy shapes.…”
Section: Shear Estimation Algorithmmentioning
confidence: 99%
“…Mellier 1999;Bartelmann & Schneider 2001;Refregier 2003;Hoekstra & Jain 2008;Munshi et al 2008) and has been shown to be the most promising probe of dark energy (Albrecht et al 2006;Peacock et al 2006). Surveys' optimization and systematics minimizations in both software and hardware have been investigated (Heymans et al 2006;Massey et al 2007a;Amara & Réfrégier 2007, 2008Paulin-Henriksson et al 2008;Amara et al 2009;Bridle et al 2009), favoring wide surveys, with well-controlled, stable Point Spread Function, with comprehensive photometric redshift follow-up. Those characteristics are shared by ambitious upcoming large area surveys, such as the Large Synoptic Survey Telescope (LSST) 5 , the Panoramic Survey Telescope & Rapid Response System (Pan-STARRS) 6 , Euclid 7 and the Joint Dark Energy Mission (JDEM) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The GREAT10 challenge is the continuation of the GREAT08 challenge (Bridle et al 2009(Bridle et al , 2010 and STEP programs (Heymans et al 2006;Massey et al 2007;Bridle et al 2010), with an increasing degree of complexity.…”
Section: The Great10 Galaxy Challenge and Its Datasetmentioning
confidence: 99%